Integrating Islamic Communication Ethics and Digital Broadcasting Practices: An Institutional Analysis of Campus-Based Islamic Media - Muhammad Randicha Hamandia; Zhila Jannati (INJECT (Interdisciplinary Journal of Communication), 2025)
There has been an observed shift in digital da’wah towards more managed communication practices in institutions involved in digital media. Even when there is an emphasis on ethical guidelines in Islamic communication studies, there has been a lack of exploration of the application of such ethical guidelines in institutional digital broadcasting. The integration between Islamic communication ethics and digital broadcasting practices will be analyzed in this research study using an institutional mode of analysis based on campus-based Islamic media institutions. This research study uses a qualitative mode of research design that focuses on a qualitative analysis of literature about current developments in Islamic communication studies and media management in conjunction with a qualitative analysis of secondary data based on a desk study of institutional data from a campus-based Indonesian Islamic broadcasting station. Thematic qualitative analysis was used in some qualitative data analysis techniques in relation to identifying patterns of ethical applications in institutional settings. The data generated findings that suggest a selective application of ethics in terms of moderation in educational responsibility according to institutional capacity. Professionalism in institutional forms is more of a behavioral aspiration in terms of structural audience address rather than a current institutional practice. Instead of generating conclusive results in research findings, this study would suggest a heuristic framework of analysis in relation to the inter-relations between institutional management and ethical guidelines in digital da’wah practices based on digital broadcasting practices.